2019
DOI: 10.12693/aphyspola.136.749
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Characterization of Fog in the Terahertz Regime

Abstract: Electromagnetic radiation at millimeter and sub-millimeter (terahertz) wavelengths are being considered for various applications, including remote sensing, wireless communications, and radars. However, wireless links implemented in millimeter wavelengths above 30 GHz suffer from absorption and dispersion effects in air, which emerge mainly due to oxygen molecules, humidity, and water droplets. Such frequency dependent atmospheric propagation effects become more severe as the frequency is increased to the terah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Preliminary experimental study was conducted in sub-millimeter waves with an artificial fog seeded by high volume 'smoke machines'. It was found that the fog generates attenuation, and group delay may affect radar accuracy [16,17]. These findings led to further experimental study of the radiation dispersive effects emerging in the presence of fog, on wireless communication links operating in mmW frequencies designated for the 5G cellular communication, which is described in this paper.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Preliminary experimental study was conducted in sub-millimeter waves with an artificial fog seeded by high volume 'smoke machines'. It was found that the fog generates attenuation, and group delay may affect radar accuracy [16,17]. These findings led to further experimental study of the radiation dispersive effects emerging in the presence of fog, on wireless communication links operating in mmW frequencies designated for the 5G cellular communication, which is described in this paper.…”
Section: Introductionmentioning
confidence: 85%
“…The visibility measurements were discussed elsewhere [17]. However, we will concentrate more on the experimental technique here.…”
Section: Visibility Measurement and Estimation Of Water Droplet Conce...mentioning
confidence: 99%
See 1 more Smart Citation
“…They are employed as detection measures in many applications, such as collision avoidance radars in automobiles [12,13]. Detecting a target with a Doppler MMW radar has several advantages compared to other remote sensing technologies operating in infrared or optical wavelengths, mainly in foggy conditions and stationary background clutter scenarios [14][15][16]. Although millimeter waves are attenuated by fog, haze, and rain [17], they still can be used for short-range detection, where optical sensors completely fail.…”
Section: Introductionmentioning
confidence: 99%